Inhibition of nitric oxide synthesis for four days induces vascular abnormalities and myocardial infarct areas but not significant arterial hypertension - Xavier-Vidal,Ricardo (2012)
BACKGROUND: Nitric oxide is an endothelium vasorelaxing factor and at least in some cases is the main cause of arterial hypertension, which is one of the most important risk factors of cardiovascular diseases. In Brazil, cardiovascular diseases are the first cause of mortality, representing about 30% of the total deaths. The L-NAME (Nω-nitro-arginine-methyl-ester) blocks the nitric oxide synthesis necessary to maintain the normal arterial pressure. OBJECTIVE: To study lesions in myocardium due to the inhibition of nitric oxide synthesis during four days (via L-NAME oral administration, concentration: 75 mgs versus 100 mL-1). METHODS: Fourteen normotensive young adults Wistar rats were submitted, during four days, to L-NAME. Six rats were utilized as the Control Group. At day 4 of the experiment, the animals were anesthetized, weighed, and their thoraxes were opened, and the cardiotomy was performed. The hearts were weighed, fixed, and processed using routine methods, and they were sectioned in 3 µm and stained. RESULTS: Abnormalities were observed in the wall of arterial vessels of any dimension, as vascular damage with increasing wall thickness related mainly to proliferation of arterial smooth muscle cell in submitted animals. Proliferation of cells in the intimal layer and its thickening were also observed in small arterial vessels (arteriole). Infarct areas were present. CONCLUSIONS: The present data suggested that inhibition of nitric oxide synthesis for four days induces vascular abnormalities and myocardial infarct areas, but not arterial hypertension.